Medical magnesium alloy with mixed powder coating on surface and preparation method thereof

By preparing a mixed powder coating containing titanium, niobium, yttrium oxide ZrO2 and hydroxyapatite on the surface of medical magnesium alloy, and using plasma spraying and hydrothermal treatment technology, the problem of excessive degradation rate and insufficient corrosion resistance in the biological body is solved, and the effect of improving the mechanical properties and biocompatibility of implanted body is achieved.

CN119800267APending Publication Date: 2025-04-11NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016491.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Medical magnesium alloys degrade too fast in biological organisms and have poor corrosion resistance, resulting in excessive pH value of local environment at the implant site and short-term large-scale release of hydrogen, affecting the growth of osteocytes and the stability of the implant.

Method used

The mixed powder coatings are prepared on the surface of medical magnesium alloys, including titanium metal powder, niobium metal powder, yttrium-stabilized ZrO2 powder and hydroxyapatite. The bond strength and biocompatibility of the coating to the substrate are enhanced by plasma spraying technology and hydrothermal treatment methods.

Benefits of technology

It improves the mechanical comprehensive performance and biological activity of medical magnesium alloy implant materials, extends the service life of the implant in the biological body, improves the matching problem between the degradation rate and the growth rate of the osteocytes, and enhances the stability of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800267A_ABST
    Figure CN119800267A_ABST
Patent Text Reader

Abstract

The invention discloses a medical magnesium alloy with a mixed powder coating on the surface and a preparation method of the medical magnesium alloy. According to the technical scheme, titanium metal powder, niobium metal powder, yttria-stabilized ZrO2 powder and hydroxyapatite powder are mixed and melted in a plasma spraying mode and then sprayed to the surface of a magnesium alloy matrix, then post-heat treatment is conducted on a mixed powder coating, and the medical magnesium alloy with the mixed powder coating on the surface is obtained. The medical magnesium alloy has the beneficial effects that the mixed powder coating on the surface of the medical magnesium alloy not only has good biological activity, is beneficial to adhesion of mesenchymal stem cells and promotes proliferation and osteogenic differentiation of bone tissues, but also has excellent wear-resistant and corrosion-resistant characteristics, and the medical magnesium alloy has good application prospects. The adverse effects caused by rapid coating falling and rapid matrix degradation of the magnesium alloy in a living body are reduced, the working stability of the magnesium alloy serving as an implant material in the living body is greatly improved, and rapid recovery of a patient is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and in particular relates to a medical magnesium alloy with a mixed powder coating on the surface and a preparation method thereof. Background Art

[0002] Among medical metal materials, magnesium and its alloys have excellent degradability and biocompatibility, making them a medical implant material with great application prospects. The elastic modulus and yield strength of medical magnesium alloys are very close to those of human bones. If medical magnesium alloys are used as implant materials, they can provide a good mechanical environment for bones, avoid the occurrence of stress shielding effects to a certain extent, and reduce the possibility of implant loosening during the healing process with human bones. At the same time, the biodegradability of medical magnesium alloys makes it unnecessary for patients to undergo secondary surgery. However, due to the rapid degradation rate of medical magnesium alloys in the body and poor corrosion resistance, the pH value of the local environment of the implant site is too high and hydrogen is released in a short period of time, which will cause the human tissue to not be completely healed, and the medical magnesium alloy loses its mechanical properties. At present, coating protection on the surface of medical magnesium alloys is an ideal method, which can greatly improve the properties of the surface of medical magnesium alloy implants and improve their stability in the human body.

[0003] Nowadays, it is more common to prepare a layer of hydroxyapatite coating on the surface of medical magnesium alloy. Hydroxyapatite (HA) has the same inorganic components as human bones, similar structures, and good biological activity and biocompatibility. After implantation into the human body, it can form a solid combined bone. However, its brittleness is too great, resulting in poor mechanical properties on the surface of medical magnesium alloy with only a simple hydroxyapatite coating. At the same time, the simple hydroxyapatite coating has low corrosion resistance and is easy to fall off and dissolve in the human body, which is not conducive to the operation of medical magnesium alloy implants in the human body. At present, some inert metal oxides can be added to the hydroxyapatite coating to improve the properties of the coating and make up for the shortcomings of the simple hydroxyapatite coating.

[0004] Titanium metal has a wide range of applications in the medical field due to its excellent corrosion resistance, biocompatibility and mechanical compatibility. Titanium can greatly improve the biological activity of implant materials and promote bone cell adhesion, proliferation and osteogenic differentiation. Niobium metal has high ductility and excellent corrosion resistance. Niobium is known as a "biophilic metal" that will not react with various liquid substances in the human body and will hardly damage biological tissues. It can be combined with organic tissues for a long time and remain harmlessly in the human body. Yttria-stabilized ZrO2 powder has good biocompatibility and can be compatible with human tissues, reducing adverse reactions to the human body. At the same time, its excellent wear resistance can extend the service life of implant materials.

[0005] Plasma spraying technology can prepare coatings with good corrosion resistance and biocompatibility on the surface of medical metal materials. Plasma spraying has high spraying efficiency and is a relatively cheap coating preparation technology. The use of plasma spraying technology to prepare a hydroxyapatite composite coating with titanium metal powder, niobium metal powder and yttria-stabilized ZrO2 powder on the surface of medical magnesium alloys is expected to improve the comprehensive mechanical properties of medical magnesium alloy implant materials, enhance the bonding strength between the coating and the substrate, and improve the stability of medical magnesium alloy implant materials working in the body. At present, there has been no use of plasma spraying technology to prepare a composite coating of titanium and niobium mixed metal powder doped with yttria-stabilized ZrO2 powder and hydroxyapatite on the surface of medical magnesium alloys. Summary of the invention

[0006] In view of the deficiencies in the existing technology, the purpose of the present invention is to provide a medical magnesium alloy with a mixed powder coating on the surface; another purpose is to provide a method for preparing the medical magnesium alloy with a mixed powder coating on the surface, which can improve the comprehensive mechanical properties of the medical magnesium alloy implant material, enhance the bonding strength between the medical magnesium alloy and the coating, and at the same time, greatly improve the bioactivity and biocompatibility of the medical magnesium alloy implant material, improve its corrosion resistance, improve the mismatch between the degradation rate of the medical magnesium alloy and the growth rate of bone cells, and improve the working stability of the medical magnesium alloy implant material.

[0007] To achieve the above objectives, the present invention adopts the following technical scheme: a medical magnesium alloy with a mixed powder coating on the surface, which is composed of a medical magnesium alloy substrate and a mixed powder coating on the surface of the medical magnesium alloy substrate, wherein the mixed powder coating includes titanium metal powder, niobium metal powder, yttria-stabilized ZrO2 powder and hydroxyapatite.

[0008] Furthermore, the thickness of the mixed powder coating is 100 μm; the mass fraction of the titanium metal powder in the mixed powder coating is 10wt~40wt%, the mass fraction of the niobium metal powder is 10wt~40wt%, and the mass fraction of the yttria-stabilized ZrO2 powder is 10wt~40wt%.

[0009] Furthermore, the medical magnesium alloy substrate is a ZK61 medical magnesium alloy substrate; the particle size of the titanium metal powder in the mixed powder coating is 50-60 μm, the particle size of the niobium metal powder is 35-75 μm, the particle size of the yttria-stabilized ZrO2 powder is 30-40 μm, and the particle size of the hydroxyapatite powder is 50-60 μm.

[0010] A method for preparing the above-mentioned medical magnesium alloy with a mixed powder coating on the surface comprises the following steps:

[0011] (1) grinding and polishing the surface of the medical magnesium alloy, ultrasonically cleaning and drying the surface of the medical magnesium alloy after the grinding and polishing, and then performing sandblasting roughening treatment on the surface of the medical magnesium alloy to obtain a medical magnesium alloy with a rough surface structure;

[0012] (2) mixing titanium metal powder, niobium metal powder, yttria-stabilized ZrO2 powder and hydroxyapatite powder to obtain a mixed powder;

[0013] (3) preheating the medical magnesium alloy with a rough surface structure obtained in step (1) to obtain a medical magnesium alloy matrix;

[0014] (4) heat treating the mixed powder obtained in step (2);

[0015] (5) spraying the mixed powder after the heat treatment in step (4) onto the surface of the medical magnesium alloy substrate obtained in step (3) by plasma spraying;

[0016] (6) The medical magnesium alloy sprayed in step (5) is subjected to post-heat treatment, and then cleaned and dried to obtain a medical magnesium alloy with a mixed powder coating on the surface.

[0017] Furthermore, in step (1), the medical magnesium alloy is cut into 50×30×5 mm; the grinding and polishing treatment is to treat the surface of the medical magnesium alloy with 800#, 1500#, and 2000# sandpaper in sequence; the ultrasonic cleaning is to place it in acetone, anhydrous ethanol, and distilled water for ultrasonic cleaning in sequence; the mesh number of the brown corundum roughened by sandblasting is 36 to 180 meshes, the sandblasting pressure is 0.2 to 0.6 MPa, the sandblasting distance is 15 to 25 cm, and the sandblasting time is 10 to 60 s.

[0018] Furthermore, in step (2), mixing is performed by ball milling.

[0019] Furthermore, in step (3), the preheating temperature is 150° C. and the holding time is 30 min.

[0020] Furthermore, in step (4), the heat treatment temperature is 80° C. and the insulation time is 30 min.

[0021] Furthermore, in step (5), the process parameters of the plasma spraying are: spraying power is 31-35 kW, powder feeding rate is 15-20 g / min, main gas argon flow rate is 40 L / min, auxiliary gas helium flow rate is 10 L / min, and spraying distance is 80 mm.

[0022] Furthermore, in step (6), the post-heat treatment is performed by hydrothermal treatment, the liquid medium of the hydrothermal treatment is Hank's solution, the equipment is a stainless steel hydrothermal synthesis reactor, the liner material of the reactor is polytetrafluoroethylene, the reactor is transferred to an oven, the temperature is 150°C, and the insulation time is 6 hours; the cleaning is performed by placing it in deionized water for ultrasonic cleaning.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention can make up for the shortcomings of a single hydroxyapatite coating by adding appropriate amounts of two metal elements, titanium and niobium, and yttrium oxide-stabilized ZrO2 powder to the hydroxyapatite coating on the surface of the magnesium alloy, and the effect is more obvious than adding any one of the elements, and it works more stably in the body. The present invention selects titanium, niobium metal powders, yttrium oxide-stabilized ZrO2 powders and hydroxyapatite with reasonable particle sizes and designs multiple comparative experiments, reasonably adjusts the mass percentage between titanium, niobium, yttrium oxide-stabilized ZrO2 powders and hydroxyapatite (HA), and selects a better ratio (the mass fractions of titanium, niobium, yttrium oxide-stabilized ZrO2 powders and hydroxyapatite powders are 10%, 10%, 20%, and 60%, respectively) to make the prepared coating effect more ideal. The magnesium alloy composite coating surface prepared by the present invention has good comprehensive mechanical properties, the bonding strength between the substrate and the coating is enhanced, the biological activity and biocompatibility are greatly improved, and it has good corrosion resistance, making the magnesium alloy implant material more scientific and reasonable.

[0025] (2) The present invention adopts a plasma spraying processing method, which has high efficiency and belongs to a relatively cheap coating preparation technology, and the prepared magnesium alloy surface composite coating can achieve the expected goal. At the same time, the present invention adopts a method of multiple comparative experiments, on the one hand, to obtain a better mixing ratio of titanium, niobium, yttrium oxide stabilized ZrO2 powder and hydroxyapatite powder, and on the other hand, to select better plasma spraying process parameters, so that the preparation process is more scientific and reasonable.

[0026] (3) The present invention performs a reasonable post-heat treatment on the sample after plasma spraying. The temperature is extremely high during the plasma spraying process. Hydroxyapatite (HA) is unstable at high temperatures (over 1350°C), and part of the hydroxyapatite (HA) will decompose into impurities such as tricalcium phosphate (TCP), tetracalcium phosphate (TP) and amorphous phase. These impurities have high solubility and are easily dissolved in the body, causing the coating to fall off quickly. The present invention adopts a heat treatment method in which the sprayed sample is placed in a stainless steel reactor at 150°C for 6 hours. This heat treatment method can not only release the residual stress inside the coating of the magnesium alloy sample during the plasma spraying process, but also strengthen the bonding strength between the magnesium alloy substrate and the composite coating, thereby effectively preventing the coating from peeling off; at the same time, it can also promote the phase transition of other amorphous calcium phosphates to hydroxyapatite, reverse the thermal decomposition of hydroxyapatite, and restore the crystallinity of hydroxyapatite to a certain extent, improve the crystallinity of the coating after spraying, reduce the specific gravity of the amorphous phase, improve the mechanical properties of the coating, and improve the working stability of the magnesium alloy implant in the body. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Comparative Example 1;

[0028] Figure 2 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Comparative Example 2;

[0029] Figure 3 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Example 1;

[0030] Figure 4 This is a locally enlarged field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Example 1;

[0031] Figure 5 This is the interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Comparative Example 1;

[0032] Figure 6 This is the interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Comparative Example 2;

[0033] Figure 7 The interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Example 1;

[0034] Figure 8 The surface hardness of the medical magnesium alloy after hydrothermal treatment in Examples 1 to 3 and Comparative Examples 1 to 2;

[0035] Fig. 9 The surface wettability of the medical magnesium alloy after hydrothermal treatment in Examples 1 to 3 and Comparative Examples 1 to 2;

[0036] Fig.10 The potentiodynamic polarization curves of the medical magnesium alloys after hydrothermal treatment in Examples 1 to 3 and Comparative Examples 1 to 2 in SBF biomimetic solution;

[0037] Fig.11 The cell activity of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Examples 1 to 3 and Comparative Examples 1 to 2;

[0038] Fig.12 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Comparative Example 2 for 5 days;

[0039] Fig.13 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Example 1 for 5 days;

[0040] Fig.14 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Example 2 for 5 days;

[0041] Fig.15 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Example 3 for 5 days. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0043] Example 1

[0044] The medical magnesium alloy with mixed powder coating on the surface of this embodiment is obtained by the following steps:

[0045] (1) Prepare ZK61 medical magnesium alloy, cut the selected medical magnesium alloy into samples with a size of 50×30×5 mm by wire cutting, and then cut the surface of ZK61 medical magnesium alloy with 800 # , 1500 # , 2000 # Sandpaper grinding and polishing treatment, placing the surface of the medical magnesium alloy after grinding and polishing in acetone, anhydrous ethanol and distilled water for ultrasonic cleaning and drying; then sandblasting the surface of the ZK61 medical magnesium alloy for roughening treatment, and then placing it in acetone, anhydrous ethanol and distilled water for ultrasonic cleaning to remove surface dirt and dry it, so as to obtain a ZK61 medical magnesium alloy with a rough surface structure;

[0046] (2) Selecting hydroxyapatite powder with a particle size of 50-60 μm, titanium metal powder with a particle size of 50-60 μm, niobium metal powder with a particle size of 35-75 μm and yttria-stabilized ZrO2 powder with a particle size of 30-40 μm, and then mixing them by ball milling according to the mass fraction of titanium metal powder of 10 wt%, niobium metal powder of 10 wt%, yttria-stabilized ZrO2 powder of 10 wt%, and hydroxyapatite powder of 70 wt%, to obtain a mixed powder; wherein the ball milling method is to use a ball mill to fully ball mill for 6 hours and then dry and sieve, the rotation speed is 200 rpm, the grinding balls are zirconium dioxide ceramic balls, the diameter of the large zirconium dioxide balls is 20 mm, the diameter of the medium balls is 10 mm, the diameter of the small balls is 6 mm, and the ball number ratio is selected as large ball: medium ball: small ball of 4:30:250;

[0047] (3) heating the ZK61 medical magnesium alloy with a rough surface structure obtained in step (1) to 150° C. and keeping the temperature for 30 min; this step is mainly to reduce the residual stress on the coating surface after spraying, which is beneficial to improving the bonding strength between the mixed powder coating and the medical magnesium alloy substrate;

[0048] (4) heat treating the mixed powder obtained in step (2) in an oven for 30 min at a holding temperature of 80° C. This step is mainly to avoid the problem of nozzle clogging due to poor fluidity of the powder caused by contact with water vapor during the spraying process;

[0049] (5) spraying the mixed powder after the heat treatment in step (4) onto the surface of the ZK61 medical magnesium alloy substrate obtained in step (3) by plasma spraying; wherein the thickness of the mixed powder coating is 100 μm, and the process parameters of the plasma spraying are: spraying power is 33 kW, powder feeding rate is 18 g / min, main gas argon flow rate is 40 L / min, auxiliary gas helium flow rate is 12 L / min, and spraying distance is 80 mm;

[0050] (6) Post-heat treatment is performed on the medical magnesium alloy after plasma spraying in step (5), and then the treated sample is placed in deionized water for ultrasonic cleaning and drying to obtain a medical magnesium alloy with a mixed powder coating on the surface; wherein the post-heat treatment adopts a hydrothermal treatment method, the sprayed medical magnesium alloy prepared in step (5) is placed in a reactor, sealed and placed in an oven, the temperature is set to 150°C, and the insulation time is 6 hours; the surface of the medical magnesium alloy substrate is coated with a mixed powder coating with a mass fraction of 10wt% titanium metal powder, a mass fraction of 10wt% niobium metal powder, a mass fraction of 10wt% yttria-stabilized ZrO2 powder, and a mass fraction of 70wt% hydroxyapatite powder.

[0051] Example 2

[0052] This embodiment is the same as Embodiment 1, except that: in the mixed powder coating, the mass fraction of titanium metal powder is 10wt%, the mass fraction of niobium metal powder is 10wt%, the mass percentage of yttria-stabilized ZrO2 powder is 20wt%, and the mass percentage of hydroxyapatite powder is 60wt%.

[0053] Example 3

[0054] This embodiment is the same as Embodiment 1, except that the mass fraction of titanium metal powder in the mixed powder coating is 10wt%, the mass fraction of niobium metal powder is 10wt%, the mass percentage of yttria-stabilized ZrO2 powder is 30wt%, and the mass percentage of hydroxyapatite powder is 50wt%.

[0055] Comparative Example 1

[0056] This comparative example is the same as Example 1, except that the mass fraction of the titanium metal powder in the mixed powder coating is 10%, and the mass percentage of the hydroxyapatite powder is 90wt%.

[0057] Comparative Example 2

[0058] This comparative example is the same as Example 1, except that the mass fraction of titanium metal powder in the mixed powder coating is 10%, the mass fraction of niobium metal powder is 10wt%, and the mass percentage of hydroxyapatite powder is 80wt%.

[0059] Analyze Examples 1 to 3 and Comparative Examples 1 to 2. Figure 1 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Comparative Example 1. Figure 2 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Comparative Example 1. Figure 1 It can be seen that the coating surface contains a large number of irregularly sized incompletely melted particles, and there are many defects such as cracks and pores. The surface is relatively rough and uneven. Figure 2 After adding Nb, the number of incompletely melted particles on the coating surface decreased, and the surface was relatively flat. This is because the thermal conductivity of Nb is about 74 times that of HA. The addition of Nb helps to slow down the cooling rate of the surrounding tissue, making the coating surface flatter and smoother. However, there are still large cracks and pores on its surface. This shows that the addition of Nb can improve the shortcomings of HA to a certain extent. Figure 3 This is a field emission scanning electron microscope image of the medical magnesium alloy after hydrothermal treatment in Example 1. Figure 4 for Figure 1From the partial magnified image, we can see that the flat stacking of the coating surface is relatively smooth and flat, the surface distribution is dense and uniform, and the cracks and voids are reduced; a large number of needle-like morphologies are found in the magnified image. These tiny needle-like structures can fill the cracks and pores in the coating, which is a key factor in improving the smoothness, uniformity and density of the coating surface. This is because ZrO2 particles are smaller in diameter than HA and Nb particles, and they themselves have a piercing effect, so that the molten ZrO2 particles are broken into smaller particles under the action of the plasma flame flow, which to a certain extent fills the holes and cracks caused by the incomplete overlap of the surface layers, making the coating surface more dense and uniform. Moreover, these needle-like structures also increase the microscopic surface area of ​​the composite coating to a certain extent, which can provide more adhesion surfaces for the growth of new bone cells. Figure 5 This is the interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Comparative Example 1. Figure 6 This is the interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Comparative Example 2. Figure 7 The interface bonding morphology of the medical magnesium alloy coating after hydrothermal treatment in Example 1 is shown in Figure 1. The coating thickness is about 100 μm, and the cross-section of the coating shows a typical layered structure. The coating and the substrate are stacked on each other, and the bonding interface is basically continuous and complete, without many pores and cracks. The interface bonding between the coating and the substrate forms an irregular staggered bite, and the bonding interface forms a strong mechanical lock. At the same time, the coating with niobium metal powder and yttrium oxide-stabilized ZrO2 powder added is tightly bonded to the substrate, has a high degree of density, and there is mutual diffusion between the coating and the substrate components, indicating that there is also a certain metallurgical bonding. Figure 8 The surface hardness of the medical magnesium alloy after hydrothermal treatment of Examples 1 to 3 and Comparative Examples 1 to 2 shows that Example 3 has the largest surface hardness, which indicates that the addition of ZrO2 can further improve its surface hardness, and as the ZrO2 content increases, its surface hardness increases more significantly. Fig. 9 The surface wettability of medical magnesium alloy after hydrothermal treatment of Examples 1 to 3 and Comparative Examples 1 to 2 is shown. The surface of the coating of Comparative Example 1 has a large number of hydroxyl groups, which enhances the adsorption of the surface to the SBF solution, thereby showing a good hydrophilic effect. The surface contact angle of Comparative Example 2 is large after adding niobium powder, which is not conducive to the later cell adhesion and growth. After continuing to add ZrO2 particles, the surface contact angle value is significantly reduced, but the contact angle value will increase slightly with the increase of ZrO2 content. This may be because with the increase of ZrO2 content, its surface is uniform and dense, and the surface is smoother. Fig.10 The potentiodynamic polarization curves of the medical magnesium alloys after hydrothermal treatment in SBF biomimetic solution of Examples 1 to 3 and Comparative Examples 1 to 2 show that compared with Comparative Example 1 (corrosion current density 1.169×10 -3 A.cm -2 ) and comparative example 2 (corrosion current density 1.148×10-3 A.cm -2 ), Example 1 adds ZrO2 (corrosion current density 5.109×10 -4 A.cm -2 ), its corrosion potential increased significantly, and the corrosion current density decreased significantly, and both decreased by 2 orders of magnitude compared with the uncoated magnesium alloy. Moreover, this trend became more obvious with the increase of ZrO2 content. This may be because with the increase of ZrO2 content, the cracks and pores on the coating surface are fully filled with fine ZrO2, which effectively inhibits the diffusion of corrosive media into the coating. Fig.11 The cell activity of BMSCs cells cultured on medical magnesium alloys after hydrothermal treatment in Examples 1 to 3 and Comparative Examples 1 to 2 can be found that the cell activity of all samples decreases with the extension of the culture time. This is because all samples will undergo varying degrees of degradation during the culture process, and the pH value of the solution and Mg 2+ Increased concentration. Fig.12 This is a fluorescence microscope image of BMSCs cells cultured on a medical magnesium alloy after hydrothermal treatment in Comparative Example 2 for 5 days. Fig.13 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Example 1 for 5 days. Fig.14 This is a fluorescence microscopy image of BMSCs cells cultured on the medical magnesium alloy after hydrothermal treatment in Example 2 for 5 days. Fig.15 This is a fluorescence microscope image of BMSCs cells cultured for 5 days on a medical magnesium alloy after hydrothermal treatment in Example 3. It can be seen that the number of cells on the surface of the sample increased significantly after adding ZrO2 compared to the sample without adding ZrO2 powder, and showed a better growth state. The high content of hydroxyapatite powder in the coating of Example 1 resulted in the release of too many calcium and phosphorus ions, which affected the microenvironment of the cells. At the same time, the low content of ZrO2 caused the material to fail early when used in vivo, thereby affecting the adhesion and growth of cells. In Example 3, due to the high content of yttrium oxide-stabilized ZrO2 powder, its hardness was too hard, which was not conducive to cell adhesion. Fig.14 The medical magnesium alloy coating of Example 2 showed good cell compatibility, which may be due to the uniform and dense surface structure of the coating after adding a certain amount of ZrO2, and its good corrosion resistance effectively inhibited the degradation of the magnesium alloy and reduced the Mg 2+ The concentration provides a favorable environment for cell proliferation and growth.

[0060] For the above analysis results, the field emission scanning electron microscopy images were obtained using a GeminiSEM300 field emission scanning electron microscope, the potentiodynamic polarization curves were obtained by testing with a CHI660C electrochemical workstation, and the cell activity was observed using a Nikon Eclipse Ti-S inverted research microscope; the fluorescence microscopy images were obtained using an EnSpire 2300 multi-label microplate reader.

[0061] The detailed description of the above embodiments is to facilitate the understanding and use of the invention by ordinary technicians in the field. It is obvious that technicians familiar with the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments. Modifications and improvements made by relevant technicians in the field based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A medical magnesium alloy with a mixed powder coating on the surface, characterized in that: The medical magnesium alloy substrate is composed of a medical magnesium alloy substrate and a mixed powder coating on the surface of the medical magnesium alloy substrate. The mixed powder coating comprises titanium metal powder, niobium metal powder, yttria-stabilized ZrO2 powder and hydroxyapatite.

2. The medical magnesium alloy with mixed powder coating on the surface according to claim 1, characterized in that: The thickness of the mixed powder coating is 100 μm; the mass fraction of titanium metal powder in the mixed powder coating is 10wt~40wt%, the mass fraction of niobium metal powder is 10wt~40wt%, and the mass fraction of yttria-stabilized ZrO2 powder is 10wt~40wt%.

3. The medical magnesium alloy with mixed powder coating on the surface according to claim 1, characterized in that: The medical magnesium alloy substrate is a ZK61 medical magnesium alloy substrate; the particle size of the titanium metal powder in the mixed powder coating is 50-60 μm, the particle size of the niobium metal powder is 35-75 μm, the particle size of the yttria-stabilized ZrO2 powder is 30-40 μm, and the particle size of the hydroxyapatite powder is 50-60 μm.

4. A method for preparing a medical magnesium alloy with a mixed powder coating on the surface as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) grinding and polishing the surface of the medical magnesium alloy, ultrasonically cleaning and drying the surface of the medical magnesium alloy after the grinding and polishing, and then performing sandblasting roughening treatment on the surface of the medical magnesium alloy to obtain a medical magnesium alloy with a rough surface structure; (2) mixing titanium metal powder, niobium metal powder, yttria-stabilized ZrO2 powder and hydroxyapatite powder to obtain a mixed powder; (3) preheating the medical magnesium alloy with a rough surface structure obtained in step (1) to obtain a medical magnesium alloy matrix; (4) heat treating the mixed powder obtained in step (2); (5) spraying the mixed powder after the heat treatment in step (4) onto the surface of the medical magnesium alloy substrate obtained in step (3) by plasma spraying; (6) The medical magnesium alloy sprayed in step (5) is subjected to post-heat treatment, and then cleaned and dried to obtain a medical magnesium alloy with a mixed powder coating on the surface.

5. The preparation method according to claim 4, characterized in that: In step (1), the medical magnesium alloy is cut into 50×30×5 mm; the grinding and polishing treatment is to treat the surface of the medical magnesium alloy with 800#, 1500#, and 2000# sandpaper in sequence; the ultrasonic cleaning is to place it in acetone, anhydrous ethanol, and distilled water for ultrasonic cleaning in sequence; the mesh number of the brown corundum roughened by sandblasting is 36 to 180 meshes, the sandblasting pressure is 0.2 to 0.6 MPa, the sandblasting distance is 15 to 25 cm, and the sandblasting time is 10 to 60 s.

6. The preparation method according to claim 4, characterized in that: In step (2), mixing is performed by ball milling.

7. The preparation method according to claim 4, characterized in that: In step (3), the preheating temperature is 150° C. and the holding time is 30 min.

8. The preparation method according to claim 4, characterized in that: In step (4), the heat treatment temperature is 80° C. and the insulation time is 30 min.

9. The preparation method according to claim 4, characterized in that: In step (5), the process parameters of the plasma spraying are: spraying power is 31-35 kW, powder feeding rate is 15-20 g / min, main gas argon flow rate is 40 L / min, auxiliary gas helium flow rate is 10 L / min, and spraying distance is 80 mm.

10. The preparation method according to claim 4, characterized in that: In step (6), the post-heat treatment is performed by hydrothermal treatment, the liquid medium of the hydrothermal treatment is Hank's solution, the equipment is a stainless steel hydrothermal synthesis reactor, the liner material of the reactor is polytetrafluoroethylene, the reactor is transferred to an oven, the temperature is 150°C, and the insulation time is 6 hours; the cleaning is performed by placing it in deionized water for ultrasonic cleaning.